STORYNOMICS IN THE DIGITAL ERA: A NEW STRATEGY FOR CREATING ENGAGING TOURIST EXPERIENCES THROUGH COMPELLING NARRATIVES - Novianty Djafri; Caroline; Muhamad Stiadi; Siti Sumiati; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
This paper presents a research study investigating the effectiveness of Storynomics as a novel strategy for enhancing consumer engagement in the tourism industry during the digital era. Recognizing the influential role of stories in inspiring connections between travelers and destinations, the study also acknowledges the significance of technology in integrating storytelling into tourism. Storynomics, the proposed approach, combines the power of storytelling with digital technology to create captivating and immersive tourist experiences. A mixed-methods research approach was employed to explore the implementation and impact of Storynomics in the tourism industry. The research commenced with a comprehensive literature review, gathering theoretical foundations and existing knowledge on storytelling, technology, and consumer engagement in tourism. This review was the basis for developing a conceptual framework for Storynomics in tourism. Following the literature review, a series of practical case studies focused on successful Storynomics implementations by tourism companies. These case studies involved qualitative interviews with industry professionals, analysis of narrative content, and examination of social media platforms and interactive applications employed by these companies. The findings from the case studies were synthesized to provide valuable insights into the application of Storynomics in the tourism industry. The study highlights how the synergy between storytelling and digital technology can generate compelling and personalized experiences, drive consumer engagement, and contribute to broader marketing objectives and business growth.